A comparison between long term measured and modeled sensible heat and momentum fluxes using a High Resolution Limited Area Model (HIRLAM ) - Anna Rutgersson (Meteorologische Zeitschrift, 2000)
The objective of this paper is to study the surface fluxes obtained by a High Resolution Limited Area Model (HIRLAM), used for weather forecasts. The question arises whether the quality of the fluxes are high enough to make HIRLAM a proper tool for performing calculations of the water and energy budgets over the Baltic Sea, which is one of the aims of the BALTEX project. Turbulent fluxes modeled by HIRLAM are compared with direct flux measurements over sea for an extended time period. The model is shown to overestimate both sensible heat and momentum flux for the studied period. The sensible heat flux for the studied period is overestimated by 8.1 W/m2 and the momentum flux is systematically overestimated by 0.03 kg/ms2 or 50 %. It is shown that the values of parameters in the surface parameterization scheme can be improved, for example will a lower value of the Charnock’s coefficient agree better with the measurements. The sensitivity of the surface scheme to changes in mean parameters is studied. It is also shown that it is of great importance to have correct values of the near surface wind speed and the temperature difference between air and sea to obtain correct fluxes.